2006
DOI: 10.1074/jbc.m605200200
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii Inhibits ERK1/2 Mitogen-activated Protein Kinase Activation Both in Vitro and in Vivo and Protects against Clostridium difficile Toxin A-induced Enteritis

Abstract: Saccharomyces boulardii (Sb), a probiotic yeast, protects against intestinal injury and inflammation caused by a wide variety of enteric pathogens, including Clostridium difficile. Given the broad range of protective effects of Sb in multiple gastrointestinal disorders, we hypothesize that Sb modulates host signaling pathways involved in intestinal inflammatory responses. In this study, we found that Sb culture supernatant (SbS) inhibits interleukin-8 production induced by C. difficile toxin A or IL-1␤ in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 38 publications
7
106
0
2
Order By: Relevance
“…Studies on the probiotic yeast S. boulardii have found that it inhibits C. difficile toxin in vitro by secreting a protease that degrades the mature protein (Castagliuolo et al, 1999) and also by modulating the gut immune response (Chen et al, 2006;Kyne et al, 2001). However, data on the recently sequenced genome of CBM588 show that, although it contains protease genes, none of them is confirmed as being secreted (unpublished data).…”
Section: Inhibition Of Toxicity In Co-culture Appears To Require Cellmentioning
confidence: 99%
“…Studies on the probiotic yeast S. boulardii have found that it inhibits C. difficile toxin in vitro by secreting a protease that degrades the mature protein (Castagliuolo et al, 1999) and also by modulating the gut immune response (Chen et al, 2006;Kyne et al, 2001). However, data on the recently sequenced genome of CBM588 show that, although it contains protease genes, none of them is confirmed as being secreted (unpublished data).…”
Section: Inhibition Of Toxicity In Co-culture Appears To Require Cellmentioning
confidence: 99%
“…Studies also indicate that S.b can be used in combination with vancomycin as therapy for relapsing CDI (37, 50). The putative mechanisms involved in the effectiveness of S.b in CDI include effects directed against the microbiome, the host, as well as C. difficile and its toxins (4,6,21,40,43). However, most of the experimental work examining the effects of S.b in CDI models has been limited to nonoutbreak-associated C. difficile strains, mostly with strain VPI10463.…”
mentioning
confidence: 99%
“…One explanation for these findings is that C. difficile toxins cause direct injury to the intestinal epithelium, which is associated with a robust host inflammatory response with neutrophil activation and recruitment leading in turn to greatly amplified intestinal injury. In fact, a wide range of anti-inflammatory agents can reduce intestinal injury in animal models of CDI (Anton et al, 2004;Chen et al, 2006;Cottrell et al, 2007;Kim et al, 2005Kim et al, , 2007Kokkotou et al, 2009;Pothoulakis et al, 1993;Warny et al, 2000). The use of combinations of antibiotic and anti-inflammatory agents to treat severe CDI in humans warrants greater attention and investigation, especially given the rising incidence of severe and fatal disease (McDonald et al, 2006;Redelings et al, 2007).…”
Section: Innate Immune Responses In CDImentioning
confidence: 99%
“…It has been suggested that differences in the intracellular effects of toxin B variants produced by toxin A-negative strains (compared to toxin B from toxin A-positive strains) may be responsible for the ability of these strains to cause disease in humans. Innate inflammatory responses that are activated by the glucosyltransferase activity of C. difficile toxins A and B include the NF-kB and MAP kinase pathways (Chae et al, 2006;Chen et al, 2006;Jefferson et al, 1999;Kim et al, 2005;Warny et al, 2000). Monocytes and macrophages are activated and a variety of proinflammatory cytokines including IL-1b, TNF-a and IL-8 are released (Jefferson et al, 1999;Linevsky et al, 1997;Sun et al, 2009;Warny et al, 2000).…”
Section: Innate Immune Responses In CDImentioning
confidence: 99%